ANALISIS PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM PENENTUAN HARGA POKOK PRODUKSI PADA PT BENGAWAN TEX - Vizhencia Azoka Puspa Nanda, Djoko Kristianto & Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this research is to know the calculation of cost of goods production with Activity-Based Costing System in PT Bengawan Tex in Surakarta. Data analysis techniques using staple production price analysis with the method of Activity Based Costing System. The research results obtained the conclusion that the calculation of cost of goods production (HPP) transparent plastic sack T45 uses calculation of companies is amounting to Rp 679,88 per sheet, while the HPP uses Activity Based Costing Rp 660.26, or There are savings of Rp 19,63 per sheet. Transparent plastic sack HPP T70 calculation based on the company amounting to Rp 1.777,55 per sheet, whereas the calculation system with Activity Based Costing Rp 1.726,23, or there are savings of Rp 51,32 per sheet. Cost of goods production (HPP) plastic sack dop T45 calculation based on the company amounting to Rp 701,56 per sheet, whereas the calculation using Activity Based Costing Rp 681,31, or there are savings of Rp 20,25 per sheet. HPP plastic sack dop T70 according to calculations of the company amounting to Rp 1.801,20 per sheet, whereas the calculation using Activity Based Costing Rp 1.749,20 or there are savings of Rp 52,00 per sheet. The determination of the price of a staple production of plastic sacks cost accounting system according to company results are higher than the calculation system with Activity Based Costing. This means the price of the staple production according to the company's more expensive than a system of Activity Based Costing.Keywords: Cost of Goods Production, Activity-Based Costing System